Effect of diethyldithiocarbamate on interleukin 2 production of patients with oral lichen planus and its clinical therapeutic efficacy - Su Meng; Qian Ding-hua; Chen Yue-han (Acta Pharmacologica Sinica, 2016)
Diethyldithiocarbamate (DTC), a biological augmenting agent specific for T cells, was applied to treat patients with incipient oral lichen planus (OLP) who had been refractory to traditional therapy. DTC was administered orally (5 mg.kg-1, twice a week) for at least 3 months. Interleukin 2 (IL-2) production and lymphocyte proliferation of peripheral blood mononuclear cells (PBMC) were measured before and after the treatment. The bioactivity of IL-2 was determined by the use of IL-2 dependent cell line CTLL-2 and human recombinant IL-2. The results indicated that both IL-2 production of PBMC and lymphocyte proliferation increased (P less than 0.01). Clinical symptoms were improved significantly. The effective rate in 30 patients was 86.7%. It is suggested that the mechanism involves that DTC improves the cellular immunity of the patients.